A randomized trial comparing the effects of sternal band and plate fixation of the sternum with that of figure-of-8 wires on sternal edge motion and quality of recovery after cardiac surgery. (1st April 2020) - Royse, Alistair G; El-Ansary, Doa; Hoang, William; Lui, Elaine; McCusker, Mark; Tivendale, Lynda; Yang, Yang; Canty, David J; Royse, Colin F
Abstract: OBJECTIVES: We sought to compare the effects of conventional wire cerclage with that of the band and plate fixation of the sternum. METHODS: A parallel randomized open-label trial with 1:1 allocation ratio compared healing after adult cardiac surgery using 'figure-of-8' stainless steel wire cerclage or a band and plate system (plates). The primary end point was maximal sternal edge displacement during active coughing of ≥2 mm in ≥2 of 4 sites measured with ultrasound by 2 assessors blinded to the other at 6 weeks postoperatively. Secondary end points at 12 weeks included ultrasound assessment, computed tomography (CT) scan and multidimensional assessment of quality of recovery using the Postoperative Quality of Recovery Scale. RESULTS: Of 50 patients, 26 received plates and 24 wires. Two patients died and 1 withdrew consent leaving 25 plates and 22 wires for primary end point analysis. Operations included 37 coronary, 5 valve and 8 combined coronary and valve procedures. At 6 weeks, less sternal movement was observed in patients with plates than those with wires, 4% (1/25) vs 32% (7/22), P = 0.018. Agreement between observers was high, kappa = 0.850. At 12 weeks, less ultrasound motion was seen in patients with plates, 0% (0/23) than those with wires, 25% (5/20), P = 0.014. Recovery from pain was higher for patients with plates 92% (22/24) than those with wires 67% (14/21), P = 0.004. CT bone edge separation was less for plates 38% (9/24) than wires 71% (15/21), P = 0.036. CT mild bone synthesis or greater was similar between patients with plates 21% (5/24) and wires 14% (3/21), P = 0.71. CONCLUSIONS: Patients receiving the band and plate system had significantly less sternal edge motion than those receiving wires, 6 and 12 weeks after cardiac surgery and experienced less pain. Clinical trial registration: clinicaltrials.gov NCT03282578.